HUBUNGAN ANTARA MINAT BACA DENGAN KEMAMPUAN KOMUNIKASI MAHASISWA FAKULTAS TARBIYAH - Munira Munira; Agus Yudiawan; Rabiudin (JURNAL PENDIDIKAN DAN KEGURUAN, 2025)
This research is based on the importance of reading interest and communication skills among students of the Faculty of Tarbiyah at IAIN Sorong. The purpose of this research is to 1) determine the reading interest of students, 2) determine the communication skills of students, and 3) determine the relationship between reading interest and communication skills of students at the Faculty of Tarbiyah, IAIN Sorong. This research uses a correlational quantitative method. The population used was 279, and by using Stratified Random Sampling, a sample of 164 was taken. Data collection techniques used questionnaires, interviews, and documentation, for validity testing using Product Moment, while reliability testing used Alpha Cronbach. Data analysis uses descriptive analysis and parametric statistical techniques. The results of the descriptive analysis show that students' reading interest falls into the low category at 59.76%, and students' communication skills also fall into the low category at 53.66%. The results of the statistical analysis using the product moment correlation technique obtained values of 0.305 and 0.152, at a significance level of 5% (>), thus the alternative hypothesis (Ha) is accepted and the null hypothesis (Ho) is rejected. It can be concluded that there is a positive and significant relationship between reading interest and communication skills among students of the Faculty of Tarbiyah at IAIN Sorong, meaning that if students have a good reading interest, it is likely that they will also have good communication skills. The implications of this research indicate that the Faculty of Tarbiyah at IAIN Sorong needs to enhance students' reading interest, as reading interest is closely related to students' communication skills.